2014
DOI: 10.1186/preaccept-2573980311437212
|View full text |Cite
|
Sign up to set email alerts
|

The Harvest suite for rapid core-genome alignment and visualization of thousands of intraspecific microbial genomes

Abstract: Whole-genome sequences are now available for many microbial species and clades, however existing whole-genome alignment methods are limited in their ability to perform sequence comparisons of multiple sequences simultaneously. Here we present the Harvest suite of core-genome alignment and visualization tools for the rapid and simultaneous analysis of thousands of intraspecific microbial strains. Harvest includes Parsnp, a fast core-genome multi-aligner, and Gingr, a dynamic visual platform. Together they provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
624
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(624 citation statements)
references
References 93 publications
0
624
0
Order By: Relevance
“…Parsnp 27 produces a core genome alignment by rapidly finding maximal exact matches (as in nucmer) which can include both genes and intergenic regions. In our test we found that it performed even better than FastTree while using less CPU time.…”
Section: Resultsmentioning
confidence: 99%
“…Parsnp 27 produces a core genome alignment by rapidly finding maximal exact matches (as in nucmer) which can include both genes and intergenic regions. In our test we found that it performed even better than FastTree while using less CPU time.…”
Section: Resultsmentioning
confidence: 99%
“…Draft genome assemblies of urogenital sourced Nm and closed reference genomes of N. meningitidis, N. gonorrheae, and N. lactamica were downloaded from PubMLST (https://pubmlst.org/neisseria/) (52). Genome assemblies were compared using Harvest (v1.1.2); a reference-independent core genome alignment and maximum-likelihood phylogeny were constructed using the Parsnp aligner and then visualized using Gingr (53). The MegAlign program in the DNASTAR Lasergene 13 suite was used for multialignments of short DNA and protein sequences by Clustal W. Allele assignments of MLST, finetyping antigens, and Bexsero Antigen Sequence Typing (54) were retrieved from the PubMLST database.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial core genome and the number of SNP differences were calculated between isolates of the same MLST type using Harvest suite 1.0 (Treangen et al ., 2014) and mega 7.0 (Kumar et al ., 2016). Phylogenetic trees were constructed using a pairwise distance matrix and the neighbour‐joining algorithm ( mega 7.0, 1000 bootstraps) based on the number of calculated SNP differences between the isolates.…”
Section: Methodsmentioning
confidence: 99%